Gas Distribution Law for the Fully Mechanized Top-Coal Caving Face in a Gassy Extra-Thick Coal Seam. (13th November 2018) - Wang, Wenlin; Wang, Fangtian; Zhao, Bin; Li, Gang
Abstract : Mine gas overflow is a serious threat to the safe and efficient longwall mining of gassy coal seams. Based on the field mining conditions and gas extraction of the fully mechanized top-coal caving face of a gassy coal mine, the space volume fraction distribution and emission (extraction rate) of gas in the face were tested by an arrangement of measuring points in the stereo grid. The isograms of gas volume fraction distribution for each measurement section and air direction in the face are drawn. The research shows that each measurement section gas volume fraction distribution is presented for an asymmetric concave curve along the vertical direction of the coal wall in the air-inlet side and the air-return side of the face; on the working face air-return side, the determination of gas volume fraction distribution of the section appears as falling straight line along the vertical direction of the coal wall. Before the first weighting, the absolute quantity of gas emission in the working face increased with the advancing of the working face, reached the maximum at the time of the first weighting, and then remained stable.